ANALISIS LOT SIZING LEAST UNIT COST UNTUK EFISIENSI BIAYA PERSEDIAAAN RESIN ALKID - Ag. Eko Susetyo (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2017)
One of the important aspects of a production that is inventory control of raw materials To have more material stock stored than what is needed by a company will not only raise the cost of interest, the cost of treatment and storage but also the possibility of the decrease of the materialsÂ´ quality which would affect the benefit of a company Therefore, this research used Lot Sizing MRP technique with Least Unit Cost (LUC) to minimize the total cost of materials stock.This research was done at Home Industry Multicoating on Resin Alkid material only in production of Nitrocelullosa Cleargloss (NC) paint. To order the material in the same amount weekly even though the use of the material is different at each time of production causes big amount of left-over to be stored. In 2015, The inventory cost of the materials by home industry method was IDR 96.741.158 in 48 times period of order and the inventory cost of materials by lot sizing MRP along with LUC was IDR 36.804.000. In 2016, after estimating the use of the materials, the inventory cost of materials by home industry method was IDR 90.248.581 in 48 times period of order whereas the inventory cost of materials by lot sizing MRP along with LUC method was IDR 33,848,581